Legendre's Differential Equation and Its Hyers-Ulam Stability - Soon-Mo Jung (Abstract and Applied Analysis)
We solve the nonhomogeneous Legendre's differential equation and apply this result to obtaining a partial solution to the Hyers-Ulam stability problem for the Legendre's equation.